Pendampingan Praktek Sholat di TK Al – Fikr sebagai Upaya Mengenalkan Rukun Islam dan Gerakan Sholat Sejak Dini - Dwi Sriwidadi; Nur Sa’adatut Daraini; Onggo Dwi Pracoyo; Mujito Mujito; Arif Rachman Putra; Didit Darmawan; Solchan Ghozali; Jahroni Jahroni; Rommy Hardyansah; Muchamad Catur Rizky (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This article explains the practice of prayer which is a problem for many children at Al-Fikr Kindergarten, Sumotuwo Village. Guidance in the practice of prayer is very important to teach, because the Day of Judgment will question the practice of prayer. This assistance aims to teach children to better understand how to pray properly and correctly. The object or target of this assistance is the children of Al-Fikr Kindergarten, Sumotuwo Village, Balongbendo District, Sidoarjo. The method used in this assistance activity is Participatory Action Research (PAR) which includes three components, namely, the research component, the behavioral component, and the participation component used in this service and assistance program. In its implementation, this assistance was carried out on Thursday, August 8, 2024. This assistance activity was carried out because most children understand prayer only from theory, while in practice most of them are less appropriate so that this problem really needs attention, namely in the form of learning assistance that is more aware of the importance of prayer for us Muslims. The result of this assistance is that children understand better how to pray properly, as seen from the difference in children's prayers before receiving assistance and afterward, which is much better. This assistance activity received a warm welcome from the Ustadzah of Al-Fikr Kindergarten, Sumotuwo Village and the guardians of the children of Al-Fikr Kindergarten and in its implementation the children were very active and enthusiastic in participating in learning activities, thus showing a change towards a better direction than before.